THE DIFFERENCES OF SPEAKING ANXIETY ACROSS ACADEMIC LEVELS AND GENDER - Alifia Eka Pristiyaputri; Mahabbatul Afiqoh; Mohammad Aryun Jauhari; Muhammad Jalaludin Al Afghani; Kurniasih Kurniasih (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2023)
Speaking anxiety poses a crucial challenge for university-level students during their speaking classes. This study aims to investigate the differences in English anxiety levels according to year level and gender at the University of Islam Malang and explore potential causes that contribute to anxiety levels. This study used a quantitative approach and employed a causal-comparative and descriptive quantitative design. Data were collected by using a 31-item FLSAS questionnaire. The subjects were freshmen and sophomores in which freshmen took an intensive course and sophomores took the public speaking course. One hundred fifteen students completed the questionnaire online. The data were analyzed by using an independent t-test and descriptive analysis. The findings revealed no statistically significant difference was found in anxiety levels between the freshmen and sophomores. Both groups exhibited moderate anxiety levels, which were approaching a high level. Besides, in terms of gender, this study did not find significant results among female and male freshmen students, but this study found there are significant results among female and male sophomore students. This study also investigated factors affecting speaking anxiety, including competitiveness, perfectionism, lack of confidence, physical and mental avoidance, fear of failure, and lack of eagerness to participate in speaking classes. All these identified factors exerted moderate influence, except for competitiveness, which demonstrated a high level of impact.